7x+3=4x+12

Simple and best practice solution for 7x+3=4x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+3=4x+12 equation:


Simplifying
7x + 3 = 4x + 12

Reorder the terms:
3 + 7x = 4x + 12

Reorder the terms:
3 + 7x = 12 + 4x

Solving
3 + 7x = 12 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
3 + 7x + -4x = 12 + 4x + -4x

Combine like terms: 7x + -4x = 3x
3 + 3x = 12 + 4x + -4x

Combine like terms: 4x + -4x = 0
3 + 3x = 12 + 0
3 + 3x = 12

Add '-3' to each side of the equation.
3 + -3 + 3x = 12 + -3

Combine like terms: 3 + -3 = 0
0 + 3x = 12 + -3
3x = 12 + -3

Combine like terms: 12 + -3 = 9
3x = 9

Divide each side by '3'.
x = 3

Simplifying
x = 3

You can always share this solution

See similar equations:

| 10x^2+78x=16 | | 4(2+5x)=20x+8 | | x(6x-7)=13 | | (x+2)(x-3)=4x | | (3x-8)(6x+5)=0 | | (8x+9)(4x-7)=0 | | x+5.2=-18.73 | | (36)(y)=14.76 | | 4.58+v=2.5 | | 8965=4 | | 11x=166 | | 3x+4=11x-6 | | 5523=0 | | 0=1111 | | 0+0=7777 | | 3y+2x=z | | 4x+9=-2x-6 | | r^2=54-3r | | -[3x+(9x+7)]=6-(3x+9) | | 10d+2dg-6d+5d-2dg= | | 2s-s+7s= | | 2x*2x+1*1-3x=5 | | 10qr-3qr+6qr-3qr= | | 14x^3+10x^2+6x= | | 2j-j+9j= | | (6Y+4)(-4Y^2-9Y+4)= | | 4+2b= | | x+5=21 | | 9n-6n+2n= | | 5-(2w-2)=3(3w-8) | | 4x^2=8+4x | | 48s+41stu-33Stu= | | 3Z-9=4Z-6 | | X^2=x+12 | | 9+3p-2p+5= | | 6X^2-18XY-7X+21Y= | | 7np-7np+4np+10np= | | 9m+9MN= | | 5x+23=13x-41 | | 2m+7n+m= | | Y-0.6Y=15 | | n^2-6n=0 | | 3r+6st+5r+3st-7st= | | 3x+2y=-9 | | -5x+3(3+2x)=7 | | 41p+37p+3pqr= | | x-7x+10=28 | | 20x+22+17x+18=90 | | 33n+32np+37n-45n+18np= | | 5x+3-4x= | | 7(2a-8)=4(2a-5) | | 2x-7y=19 | | 16+3y=5y+12 | | 4(3x-2)-4(x-2)=2 | | 5(b-6)+15=15 | | 6(7x-(7-2y+2x)+5y)= | | 14x-8=13x-10 | | MN+4MN+5MN-10MN+5MN= | | 1(x+1)=5 | | 1+4x^2=8X | | 6k+7=4+12k | | 9t^2+14-17t+6t-8t^2=0 | | X^2+6x=9 | | 10m-4(3m+7)+6m=0 | | 5x^10-4x^11=1 |

Equations solver categories